Experimental studies of the influence of deformations in nodal joints on the stress-strain state in a full-scale support made of MIC-C - V. N. Dolzhikov; E. N. Dolzhikova (Vestnik MGSU)
Introduction. Deformations in bolted joints of elements in theoretical studies were taken into account by introducing linear deformation modules of elements instead of elasticity modules. The necessity to take into account the deformability of the interfaces is due to the fact that rigid nodes of rod structures are actually deformable, while hinged ones are able to perceive moments. The pliability of bolted joints leads to increase in the total deformations of structural structures by 40 % and change in the forces in the elements by up to 30 %. In some cases, the forces in the elements change the sign.Materials and methods. The experiment was carried out with the assistance of Bridge Crew No. 81 on a full-scale design of an auxiliary support for the semi-mounted assembly of the bridge span structure, coordinated with the Central Research Institute and Glavmoststroy. The vertical load on the support was created by the weight of the bridge superstructure being mounted, the horizontal load was created using a cable attached to a C-100 bulldozer tractor. Cable tension control with a bulldozer was performed with a dynamometer. Relative deformations were measured using beacons drilled into the body of the elements using a strainmeter with a base of 505 mm and a division price of 0.01 mm. The displacements in the bolted joints of the elements were measured with a strainmeter with a base of 125 mm.Results. The experimental force values obtained in the presence of displacements in the joints of the auxiliary support are quite close to the calculation results according to the proposed method. The average value of the ratio of experimental forces in the elements, taking into account displacements in the joints, to the values of theoretical forces without displacements (according to the hinge scheme) and to the values of theoretical forces, taking into account displacements in bolted joints, according to the proposed methodology, are 0.84 and 1.05, respectively. The average relative change in forces caused by displacements in the joints of the elements is 48 % for braces and 18 % for racks.Conclusions. It is shown that the experimental values of the forces in the elements are close to their calculated values determined by the calculated modules of linear deformation. At the same time, the magnitude of the forces differs significantly from their values obtained by calculation without taking into account the displacements in the elements.